Analysis of land speculation in the urban fringe of Lagos, Nigeria. (4th May 2018) - Thontteh, Esther Oromidayo; Babarinde, Jacob Adejare
Abstract: This study investigates and analyses factors motivating land speculators operating in the urban fringe of Lagos, Nigeria. The paper, in addition to contributing to literature, is the first known attempt to study the behaviour of land speculators in the urban fringe of a growing African megacity with a population in excess of 17 million. Between September and December 2016, two questionnaire surveys were separately administered with a representative random sample of 97 members of the Real Estate Developers Association of Nigeria (REDAN), including 14 members who are actively operating their land, and 12 senior officials of the Lagos Land Bureau. Principal component matrix was constructed to identify the most critical factors determining such acquisitions. Findings reveal seven themed-principal components and a speculative motive that is not related to any desire to resolve the lingering housing supply problem. Land speculators indicated their tendency to acquire for future sale, promote self-esteem and pursue private profiteering business. Furthermore, regulatory lapses, location preference, informality of land title as well as relatively cheap land promote speculative land acquisitions without actual development. Hence, to develop smart cities for solving the lingering housing problem in Nigeria, speculative activities of land developers must be thoughtfully controlled.